AKULTURASI ISLAM SUNDA (Kajian terhadap Tradisi Hajat Sasih) - Abdurrahman Misno Bambang (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This research is about Idul Adha festival which is combined withHajat Sasih, a ritual that is spread out in Kampung Naga. Phenomenologicalapproach with ethno science paradigm by James P. Spradley isused to record the festival. It has been found that the festival is withoutslaughtering the livestock and the Hajat Sasih ritual is dominated thefestival. Hajat Sasih is a kind of thankfulness to God by visiting the cemeteryof the ancestors; Sembah Dalem Eyang Singaparana besides it isalso a special moment for the people to get the benefit of silaturahmi,ziarah kubur and tumpeng which are blessed by the senior villager. Thepeople are presenting a gift to religious leaders and village leaders.